2015
DOI: 10.1097/mrr.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Tampa Scale of Kinesiophobia for Parkinson’s disease

Abstract: The aim of this study was to validate the Tampa Scale of Kinesiophobia for Parkinson's disease (TSK-PD). This was a cross-sectional evaluation of the psychometric properties of an adapted questionnaire. The psychometric testing included confirmatory factor analysis, reliability by internal consistency (Cronbach's α) and test-retest reliability (intraclass correlation coefficient), construct validity by comparing TSK-PD with the Falls Efficacy Scale-International (FES-I), the Movement Disorder Society - Unified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…The prevalence of this problem and its significance meant that kinesiophobia has been and continues to be studied in an increasing number of different disease entities [ 25 , 26 , 27 , 28 , 29 ]. For neurological diseases, there are few empirical studies devoted to kinesiophobia in neurological diseases [ 30 , 31 , 32 ] and this problem is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of this problem and its significance meant that kinesiophobia has been and continues to be studied in an increasing number of different disease entities [ 25 , 26 , 27 , 28 , 29 ]. For neurological diseases, there are few empirical studies devoted to kinesiophobia in neurological diseases [ 30 , 31 , 32 ] and this problem is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature found individual works carried out using TSK—people with PD [ 30 ], MS [ 31 ], S [ 32 ] as well as people with dystonia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, avoidance behaviour as an adaptation to pain in the long term would develop disuse, disability, and depression [5]. Kinesiophobia had been widely assessed in various conditions including Parkinson's disease, fibromyalgia, spinal stenosis, and low back pain (LBP) [69]. …”
Section: Introductionmentioning
confidence: 99%
“…The psychometric properties of the scale have been checked in different languages [913] and for different pain disorders (e.g., low back pain [14, 15], neck pain [13], Parkinson's disease [16] and heart failure [17]). The Tampa Scale for Kinesiophobia for Temporomandibular Disorders (TSK-TMD) was recently developed by Visscher et al to assess of fear of movement in TMD patients [18].…”
Section: Introductionmentioning
confidence: 99%